Isolasi, Karakterisasi, dan Uji Aktivitas Antioksidan Senyawa Turunan Kuersetin dari Kulit Batang Melicope quercifolia - Abror Rahman; Ifana Mahardika; Ratih Dewi Saputri; Tjitjik Srie Tjahjandarie; Mulyadi Tanjung (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2020)
Two quercetin derivatives, pachypodol (1) and ayanin (2) were isolated from the stem bark of Melicope quercifolia (B.S. William) Ridl. Their structures were determined based on spectroscopic data such as UV, IR, MS and NMR. Compounds 1–2 were evaluated for their antioxidant against DPPH radical showing their IC50 were 254 ± 10 and 38.55 ± 0.02 µg/mL, respectively.